2018
DOI: 10.1111/jpi.12494
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger of Arabidopsis thaliana 6 is involved in melatonin‐mediated auxin signaling through interacting INDETERMINATE DOMAIN15 and INDOLE‐3‐ACETIC ACID 17

Abstract: Although accumulating evidence demonstrates the cross talk between melatonin and auxin as derivatives of tryptophan, the underlying signaling events remain unclear. In this study, we found that melatonin and auxin mediated the transcriptional levels of zinc finger of Arabidopsis thaliana (ZAT6) in a mutually antagonistic manner. ZAT6 negatively modulated the endogenous auxin level, and ZAT6 knockdown plants were less sensitive to melatonin-regulated auxin biosynthesis, indicating its involvement in melatonin-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Several studies have reported possible altered IAA levels in response to melatonin treatment or by melatonin‐rich transgenic plants . To investigate the possible relationship between melatonin and IAA, we measured IAA levels in the melatonin‐deficient rice plants using an ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported possible altered IAA levels in response to melatonin treatment or by melatonin‐rich transgenic plants . To investigate the possible relationship between melatonin and IAA, we measured IAA levels in the melatonin‐deficient rice plants using an ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin is essential for normal growth and development, such as stomatal closure, the auxin signaling pathway, starch synthesis, plant regeneration, and root formation, as well as for defense against an array of biotic and abiotic stressors, including high light, pathogens, salt, senescence, and high temperature, among others . The functional roles of melatonin in plants are associated with crosstalk with plant hormones, such as auxin, cytokinin, salicylic acid, and abscisic acid …”
Section: Introductionmentioning
confidence: 99%
“…It is known that endogenous auxin (IAA) levels are reduced by melatonin (1, 50, 100 and 200 μM) when supplemented in the growth medium in Arabidopsis by enhancing expression of Zinc Finger transcription factor ZAT6 [72]. Interestingly in the same study, ZAT6 showed no direct binding to TACAAT motifs in the promoter of the auxin biosynthetic gene YUC2 as analysed by ChIP-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The IDD proteins directly bind to the promoter regions of TAA1 , PIN1 , and YUC5 and activate their expression. IDD -regulated auxin signaling might be further regulated by ZAT6 [68]. Further study of crosstalk between hormone metabolism and the surrounding environment will lead to a better understanding of the role of IDD proteins in the regulation of hormonal signaling.…”
Section: Biological Functions Of Iddsmentioning
confidence: 99%